Diastolic Dysfunction Is a Predictor of Poor Survival in Patients with Decompensated Cirrhosis. (2nd December 2021) - Behera, Manas Kumar; Swain, Surendra Nath; Sahu, Manoj Kumar; Behera, Gaurav Kumar; Mishra, Debakanta; Narayan, Jimmy; Singh, Ayaskant; Agarwal, Shobhit; Mallick, Pradeep Kumar
Abstract : Background . Left ventricular diastolic dysfunction (LVDD) appears to be the earliest cardiac disturbance in cirrhosis patients. There are many previous reports reporting the significance of severity of LVDD on the outcome of liver transplantation or TIPS insertion, a few Indian studies have addressed the role of LVDD on survival in decompensated cirrhosis. The objective of this study is to assess the effect of LVDD on the survival of decompensated cirrhotic patients. Methods . We prospectively evaluated 92 decompensated cirrhotic patients from April 2015 to March 2017 at IMS and SUM Hospital, Bhubaneswar, India. 2D echocardiography with tissue Doppler imaging was used to evaluate cardiac function, as per the American society of echocardiography guidelines. The primary endpoint was to evaluate the effect of LVDD on overall mortality. Results . Ninety-two decompensated cirrhotic patients were evaluated in this prospective cohort study. Twenty-eight out of 92 patients (30%) died due to liver-related complications after a follow-up of 24 months. The decompensated cirrhotic patients with MELD   score ≥ 15 had a significantly higher E / e ′ ratio (11.94 ± 4.24 vs. 8.74 ± 3.32, p < 0.001 ) suggesting severe LV dysfunction in advanced cirrhosis. Patients with E / e ′   ratio > 10 had significantly higher MELD score and Child-Pugh score (19.88 ± 7.72 vs. 14.31 ± 5.83 ; 10.25 ± 1.74 vs. 9.02 ± 1.74, p < 0.01, respectively) as compared to theE / e ′   ratio < 10 group. In Cox proportional hazard multivariate analysis, E / e ′ ≥ 10 (HR 2.72, 95% CI 1.07-6.9, p = 0.03 ) and serum albumin (HR 0.32, 95% CI 0.14-0.7, p < 0.01 ) were found to be independent predictors of mortality in decompensated cirrhotic patients. Conclusion : The presence of LVDD and low serum albumin were independent predictors of mortality in decompensated cirrhotic patients. Hence, LVDD is an indicator of advanced cirrhosis and mortality.